Face Mask Detector and Temperature Skrining Using IoT - Sari Muthia Silalahi; Paul Nainggolan; Christine Hutahaean; Grace Siburian (Proklamasi 45 University, 2022)
The coronavirus outbreak hit the world in early 2020, including Indonesia. Health protocols such as wearing masks, maintaining distance, checking body temperature, and washing hands are carried out to prevent the spread of the coronavirus. Therefore, this research aims to build an Internet of Things (IoT) based system to detect the use of masks and body temperature measurements as well as the use of doorstops as a condition of whether users can enter the environment or not. Observations, questionnaires, and interviews were also conducted to collect data to see the use of existing health protocols and respondents' opinions on the application of IoT in the health sector, especially the application of health protocols. The observation results showed that there were still many people who did not use masks and did not check their body temperature if they wanted to enter a place. The results of questionnaires and interviews were obtained with 93% saying yes that the built product was feasible and would help the spread of the coronavirus. The implementation of Arduino system design, ultrasonic sensors, python programming, and OpenCV resulted in a hardware design that is able to detect masks and body temperature without direct interaction between security officers and guests/students. The result is that if you don't use a mask, the alarm sounds, but if you wear a mask, the alarm doesn't sound. If the temperature is detected above 37.50 C, the servo will be closed which means that the user cannot enter the location, while if the temperature is detected below 37.50 C, the servo will open.